Iron Oxide Versus Fe55Pt45/Fe3O4: Improved Magnetic Properties of Core/Shell Nanoparticles for Biomedical Applications - Varanda, L. C.; Imaizumi, M. [UNESP]; Santos, F. J. [UNESP]; Jafelicci, M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2008)
In this paper, synthesis of the Fe55Pt45/Fe3O4 core/shell structured nanoparticles using the modified polyol process combined with the seed-mediated growth method is reported. Iron oxide shell thickness was tuned controlling the Fe(acac)(3)/FePt seeds in the reaction medium. Annealing of the core/shell structure leads to iron-rich layer formation around the hard FePt phase in the nanoparticle core. However, the 2 nm Fe3O4 shell thickness seems to be the limit to obtain the enhanced magnetization close to the alpha-Fe and preserving an iron oxide shell after annealing at 500 degrees C for 30 min in a reducing atmosphere. The presence of both the oxide layer on nanoparticle surface and an intermediate iron-rich FePt layer after annealing promote strong decreases in the coercive field of the 2-nm-oxide shell thickness. These annealed nanoparticles were functionalized with dextran, presenting the enhanced characteristics for biomedical applications such as higher magnetization, very low coercivity, and a slightly iron oxide passivated layer, which leads an easy functionalization and decreases the nanoparticle toxicity.
Keywords: Biomedical applications; dextran coating; iron oxide/FePt core shell structure; magnetic nanoparticles